The effectiveness of monetary policy in tackling inflation in emerging economy - Grace N. Ofoegbu, Vincent A. Onodugo, Oluchukwu F. Anowor (Opción, 2019)
This study decided to investigate the success and failure of monetary policy in tackling inflation in order to achieve desired economic objectives by making use of the econometric procedure in estimating the relationship between the variables. The method of data analysis is the ordinary least square1 multiple regression. The results of our analyses showed that the instruments of monetary policy would have had a greater impact on inflation if inflation were not of structural nature. As a conclusion, the financial system needs to be strong, sound, viable, and shock-resilience in order to achieve the standard of a sustainable economy.